Chakana bank xizmatlari samaradorligini oshirish: Turonbank ATB misolida (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the issue of increasing the practical efficiency of retail banking services in Uzbekistan using the example of Turonbank JSCB. The introduction explains the relevance of the topic and digital changes in the banking sector. The methods section clearly explains the sources of information, selected approaches and criteria. The analysis section systematically describes real business processes in the channel, segment and product segments, the system of key indicators, as well as observations on seasonality and load peaks. The results highlight the expansion of digital channels, reduction of queue pressure and changes in customer experience. The discussion offers specific solutions in the areas of infrastructure, customer experience and human capital. The conclusions and recommendations section summarizes the expected benefits for the bank and customers